2017
DOI: 10.1055/s-0037-1598157
|View full text |Cite
|
Sign up to set email alerts
|

Considerations in Stoma Reversal

Abstract: Temporary stomas are frequently used in the management of diverticulitis, colorectal cancer, and inflammatory bowel disease. These temporary stomas are used to try to mitigate septic complications from anastomotic leaks and to avoid the need for reoperation. Once acute medical conditions have improved and after the anastomosis has been proven to be healed, stomas can be reversed. Contrast enemas, digital rectal examination, and endoscopic evaluation are used to evaluate the anastomosis prior to reversal. Stoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
1
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 52 publications
3
66
1
11
Order By: Relevance
“…Once the acute medical conditions improves and after the anastomosis has been proven to be healed, the stoma can be reversed. [24] Ileostomy closure (<3 months) is practical and safe. [25] However, in the present study, the median interval between stoma formation and closure was 8.5 months (range: 4–28 months).…”
Section: Discussionmentioning
confidence: 99%
“…Once the acute medical conditions improves and after the anastomosis has been proven to be healed, the stoma can be reversed. [24] Ileostomy closure (<3 months) is practical and safe. [25] However, in the present study, the median interval between stoma formation and closure was 8.5 months (range: 4–28 months).…”
Section: Discussionmentioning
confidence: 99%
“…Closure rates are lower than 50% in most published series [ 4 10 ]. A large retrospective study showed that better chances of closure were found in nonneoplastic cases, younger age, male gender, and a low Charlson comorbidity index [ 11 13 ]. Despite HR still being generally performed by conventional open surgery, in recent years there has been increasing interest in the application of minimally invasive surgery (MIS) to reduce morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…When creating a stoma, the surgeon usually selects a stoma that may be technically easier to close. The rate of the inability to close temporary stomata ranges from 6% to 32%, which can be up to 50% after the Hartmann procedure [4] . Santulli enterostomies are superior over other conventional types of stomas in that they can be closed extraperitoneally or even under local anesthesia.…”
Section: Discussionmentioning
confidence: 99%